Factors Influencing Behaviors in Preventing COVID-19 of Teachers and Caregivers in Child Care Centers - Witoonsakul, Pattaranuch; Chaisuwan, Chayapa; Rungamornrat, Somsiri (Nursing Science Journal of Thailand, 2021)
Purpose: To examine the predictive power of self-efficacy, health literacy, and support from the provincial administrative organizations on behaviors of teachers or caregivers in preventing infection and transmission of COVID-19 in child care centers. Design: Correlational predictive design. Methods: The sample comprised of 100 teachers or caregivers in child care centers. This study was done with a convenience sampling who met the inclusion criteria. The instruments for data collection included a demographic questionnaire, a self-efficacy questionnaire, a health literacy questionnaire, a questionnaire on perceived support from provincial administrative organizations, and a COVID-19 preventive behaviors questionnaire. The data were analyzed using descriptive statistics and stepwise multiple regression. Main findings: Perceived self-efficacy and support from the provincial administrative organizations could be jointly predicted teachers’ or caregivers’ behaviors in preventing infection and transmission of COVID-19 in child care centers 33% (R2 = .33, F = 23.33, p < .001). The factors that significantly predicted teachers’ or caregivers’ behaviors in preventing infection and transmission of COVID-19 in child care centers were perceived self-efficacy (β = .46, p < .001) and support from the provincial administrative organizations (β = .21, p = .020). Conclusion and recommendations: Perceived self-efficacy and support from the provincial administrative organizations are key predictors of behaviors in preventing infection and transmission of COVID-19. The healthcare team will be able to use the research findings to guide the development of programs that promote preventive behaviors of COVID-19 infection and transmission for teachers or caregivers in child care centers by enhancing perceived self-efficacy and support from the provincial administrative organizations.